Analisis Kadar Hidroquinon Pada Sabun Pembersih Wajah Batangan yang Diperjualbelikan di Pasar - Rustiah, Waode; Muharram, Andi Fatmawati; Arisanti, Dewi; Muawanah, Muawanah; A. Salim, Indra Permata; Amelia, Kiki Putri (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2024)
Bar soap is a skin cleansing preparation in solid form made from soap with the addition of desired ingredients, be they natural ingredients or dangerous chemicals. Hydroquinone is a dangerous chemical which, if added excessively to facial cleansing soap, can cause hyperpigmentation on the skin. The use of hydroqunon according to BPOM regulation no. 18 of 2015 is included in the class of hard drugs. Hydroquinone is prohibited from being used because it has dangerous side effects such as skin irritation, facial redness such as a burning sensation and can also cause black spots on the face. This type of research is a laboratory observational study which aims to analyze the hydroquinone levels in bar facial cleansing soap that is sold at the Minasa Maupa market, Sungguminasa, Gowa Regency. The sampling technique was carried out by purposive sampling. The samples were tested qualitatively using the thin layer chromatography method and if positive results were obtained, quantitative analysis was continued using the UV-Vis spectrophotometry method. From the research results of 10 samples of bar facial cleansing soap, 1 sample was positive for containing hydroquinone, indicated by the presence of stains when observed under a UV lamp with an Rf value of 0.427, while the standard Rf value was 0.438. Meanwhile, the other 9 samples did not contain stains so the Rf value could not be calculated. Next, the positive samples were continued with quantitative analysis to obtain a hydroquinone level of 0.013%. The levels obtained were stated to be still below the standards set by BPOM No. 18 of 2015 which amounted to 0.02%